Consumer Preferences of Packaged Cooking Oil in Bandar Lampung City - Zainal Abidin; Marsha Dinda Maharani; Fembriarti Erry Prasmatiwi (Economics Development Analysis Journal, 2021)
Packaged cooking oil is a food product that is needed by every households. In the market, packaged oil products have various brands and packaging forms such as refillable plastic packaging, plastic bottles, and plastic jerrycans. The purpose of this study is to determine the combination of attributes packaged cooking oil that are most preferred by consumers and attribute that have the highest importance value for consumers of packaged cooking oil. The research method uses survey methods and the analytical method used is conjoint analysis to determine consumer preferences for packaged cooking oil. research reveals more detailed results. Most research consumers are between 38-52 years old, with 4-6 family members, total family income between Rp 8,000,000-Rp 15,000,000 per month, and the last education of housewives is high school. The most widely used brand of packaged cooking oil is Bimoli with the type of plastic packaging and the size of 2 liters, with an average household consumption of 3.714 liters per month. Based on conjoint analysis, it is concluded that consumers prefers price combination of Rp 11,000-Rp 13,000 per l, 2 liters packaging size, clear, and the bottled packaging. The most important attribute is the clarity of packaged cooking oil with value of 29,693.